Rancang Bangun Aplikasi Pemetaan Pelanggan Indibiz Berbasis Web Pada PT. Telkom Indonesia TBK Cabang Kota Prabumulih - Dinda Pralaka; Muchlis Muchlis; Jepri Yandi (STEKOM PRESS, 2024)
Current technological advances have made the need for information technology very necessary. With the existence of web-based geographic information system technology, it can help PT. Telkom Indonesia Tbk Prabumulih City Branch to digitize every Indibiz customer and target area for Indibiz products. The aim of this research is to create a web-based Indibiz customer mapping information system and to improve technician performance in matters concerning Indibiz. The research method used is descriptive qualitative, the Waterfall method as a system development method and UML as a design tool. The application was built using a website with the php programming language, a mysql database, and printing data using pdf files.